Quantifying the Effects of Phosphate Solubilising Fungi and Phosphorus Chemical Fertilizer on Phosphorous Economy and Productivity of Rainfed Castor on Alfisols - Ramanjaneyulu, A. V.; Kumar, M. V. Nagesh; Madhavi, A.; Neelima, T. L.; Suresh, G. (International Journal of Economic Plants, 2021)
A three year (kharif 2011-12, 2012-13 and 2013-14) field study was conducted to understand the effect of seed treatment with biophos biofertilizer at different phosphorus levels on phosphorus economy, growth and productivity of rainfed castor, at Regional Agricultural Research Station, Palem, Professor Jayashankar Telangana State Agricultural University, India. The experiment had eight treatments including control, seed treatment with biophos (30 g inoculant per 50 g seed), 20, 40 and 60 P2O5 ha-1 with and without biophos, replicated thrice in a randomized block design. The seed yield was relatively low during 2011 and higher in 2012 and 2013. It increased linearly from no phosphorus application upto 40 kg P2O5 ha-1 afterwhich it declined. Biophos was very effective at lower or medium phosphorus dose than at higher P dose. The pooled data indicated that supply of 20 kg P2O5 ha-1 besides biophos seed treatment with higher seed yield (1439 kg ha-1) has significantly outyielded 60 kg P2O5 ha-1 (1254 kg ha-1) and control (1098 kg ha-1), but, at par with other phosphorus doses. However, gross returns (INR 46,555 ha-1), net returns (INR 26,071 ha-1) and B:C ratio (2.26) were greater due to integrated application of 20 kg P2O5 ha-1 andseed treatment with biophos@30g inoculant 50 g-1 seed only. Besides, this helped in saving of 20 kg P2O5 ha-1 against the recommended dose of 40 P2O5 ha-1.